1996
DOI: 10.1109/10.532130
|View full text |Cite
|
Sign up to set email alerts
|

Measures of postural steadiness: differences between healthy young and elderly adults

Abstract: Measures of postural steadiness are used to characterize the dynamics of the postural control system associated with maintaining balance during quiet standing. The objective of this study was to evaluate the relative sensitivity of center-of-pressure (COP)-based measures to changes in postural steadiness related to age. A variety of time and frequency domain measures of postural steadiness were compared between a group of twenty healthy young adults (21-35 years) and a group of twenty healthy elderly adults (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

75
1,169
14
47

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,483 publications
(1,366 citation statements)
references
References 30 publications
75
1,169
14
47
Order By: Relevance
“…Corroborating this approach, a strong correlation has been shown between muscle lateral displacements and force fluctuations during isometric contractions (Yoshitake et al 2008). Hence, the current study indirectly assessed the variability of tangential forces by the total excursion of CoP, which represents the total length of the CoP path during a given time interval (Prieto et al 1996), thus assessing the lateral displacements of quasi-static forces. VAS scores were recorded during all contractions and the mean VAS score was extracted from the same time window used for the force parameters.…”
Section: Discussionmentioning
confidence: 91%
“…Corroborating this approach, a strong correlation has been shown between muscle lateral displacements and force fluctuations during isometric contractions (Yoshitake et al 2008). Hence, the current study indirectly assessed the variability of tangential forces by the total excursion of CoP, which represents the total length of the CoP path during a given time interval (Prieto et al 1996), thus assessing the lateral displacements of quasi-static forces. VAS scores were recorded during all contractions and the mean VAS score was extracted from the same time window used for the force parameters.…”
Section: Discussionmentioning
confidence: 91%
“…Variance was characterized by: 1) root-mean-square (RMS) amplitude of the signals, 2) path-length (PATH), and 3) 95% ellipse area (EA) (Prieto et al 1996). These were computed from the first 40 seconds of each trial.…”
Section: Discussionmentioning
confidence: 99%
“…The fluctuations of the COP were analyzed with root mean square distance (RDIST), the 95% confidence ellipse area (AREA-CE), and the mean velocity (MVELO). [21][22][23] During the dynamic stability test, the ability to voluntarily displace the COP to a maximum distance without losing balance was assessed. 24 Eight targets were presented on the screen at 45-degree angles from one another around the center.…”
Section: Exercise Performancementioning
confidence: 99%
“…It has been earlier shown that during static postural stability test, RDIST and AREA-CE can be related to the effectiveness of, or the stability achieved by, the postural control system; and MVELO has been related to the amount of regulatory activity associated with this level of stability. [21][22][23] The increased AREA-SZ on the other hand has been related to an enhancement of muscle strength. 24 Consequently, we can also assume a non-specific effect of the training on the postural control mechanisms after our balance training program.…”
Section: Improved Balance Functionmentioning
confidence: 99%